Enhancing informatics learning through android-based interactive media: A development study with the ADDIE model - Dewi, Siti Karunia; Surur, Miftahus; Jaya, Firman (Asatiza: Jurnal Pendidikan, 2025)
Initial observations in Grade X Informatics classes at SMA Negeri 1 Panji identified a significant pedagogical challenge: low student motivation and engagement, largely due to the perceived complexity of the subject matter. To address this issue, Android-based learning media was proposed as an innovative solution, leveraging its ability to present content dynamically through integrated multimedia elements such as images, videos, animations, and interactive quizzes. This research and development (R&D) study aimed to design and implement such media to increase student participation, improve conceptual understanding, and create a more interactive learning environment. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected from 19 Grade X students, one subject teacher (serving as a material expert), and a media expert (holding a Master’s degree in Computer Science). Results indicated that the developed Android-based interactive learning media, named "Bitnesia," is highly suitable for educational use. This conclusion is supported by outstanding validation outcomes, with media expert, material expert, and student effectiveness tests all scoring ≥90%. The study affirms that a well-designed learning media application can significantly contribute to a stimulating and effective Informatics learning experience.